The Role of Oxidative Stress and Hormones in Controlling Obesity - Di Domenico, Marina; Pinto, Federica; Quagliuolo, Lucio; Contaldo, Maria; Settembre, Giuliana; Romano, Antonio; Coppola, Mario; Ferati, Kenan; Bexheti-Ferati, Arbëresha; Sciarra, Antonella; Nicoletti, Giovanni Francesco; Ferraro, Giuseppe Andrea; et al. (Frontiers in Endocrinology, 2019)
The accumulation of adipose tissue in the body occurs because the energy introduced with food and drink exceeds that expense, but to understand why this imbalance is established and why it is maintained over time, it is important to consider the main causes and risk factors of excess weight. In this review we will refer to the main factors linked to obesity, starting from oxidative stress to hormonal factors including the role of obesity in breast cancer. Among the many hypotheses formulated on the aetiopathology of obesity, a key role can be attributed to the relationship between stress oxidative and intestinal microbiota. Multiple evidences tend to show that genetic, epigenetic and lifestyle factors contribute to determine in the obese an imbalance of the redox balance correlated with the alteration of the intestinal microbial flora. Obesity acts negatively on the wound healing. Artificial dermis is suitable for use in full-thickness skin defect wounds and used as alternative materials for traditional treatment for the formation of new dermis-like tissue. Medical interventions aimed not only at modifying the caloric intake, but also to modulate and improve the composition of diet with the aim of rebalancing the microbiota-redox state axis therefore appear, even more than in the past, promising tools in the treatment of obesity.